2020
DOI: 10.3390/app10238378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preheating Temperatures and RAP Characteristics on the Activation of RAP Binder

Abstract: Reclaimed asphalt pavement (RAP) is preheated to 120 °C or lower in hot central plant recycling due to specification and equipment limitations. However, the insufficient activation of reclaimed asphalt (RA) caused by low preheating temperature may affect the final properties of reclaimed asphalt mixtures (RAM) and lead to insufficient utilization of RA binder. This study evaluated the influence of preheating temperature and aging of RA binder on binder activation by producing specimens with 100% RAP. The volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Some researchers focus on binder activation within RAP [25][26][27][28]. Preheating temperature and RAP source were generally considered in previous studies, and both of them were found to have a significant impact on the activation of RAP binders [25,29,30]. Mechanical separation only changes the asphalt content of RAP without changing the binder properties of RAP.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers focus on binder activation within RAP [25][26][27][28]. Preheating temperature and RAP source were generally considered in previous studies, and both of them were found to have a significant impact on the activation of RAP binders [25,29,30]. Mechanical separation only changes the asphalt content of RAP without changing the binder properties of RAP.…”
Section: Introductionmentioning
confidence: 99%
“…However, bitumen oxidation due to different aging conditions (e.g., mixing, laying, and environmental conditions) is still an open challenge in the use of RAP to design new mixtures [ 50 ]. Chemical and rheological properties of rejuvenated binders can differ from those of virgin bitumen and require further analyses [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the RAP percentage within the WMA mixture is related to the quantity of the used additive in the mix; in other words, the selected additive can be considered as a rejuvenator or recycling agent for the aged RAP binder within the recycled WMA mixtures [16]. According to previous studies, the RAP needs to be preheated and mixed at a specific range of temperatures (120-180 • C) in order to activate the RAP binder and make it effective in combining with the virgin one [31]. Depending on the RAP percentages within the mixtures, mixing and compaction temperatures have to be selected on that basis.…”
mentioning
confidence: 99%